Mayavini Sarsi (Circe): Devkota’s Reworking to Western Myths - Chalise, Keshav Raj (Literary Studies, 2020)
Laxmi Prasad Devkota, celebrated poet as the Mahakavi or Poet the Great wasborn in 1966 BS. Writing in distinct style from the tradition, Devkota has broken the convention in Nepalese writing, both in form and content, though he was in the difficult mode of free expression due to Rana observation over writings and even the discouraging situation on free thinking and creative writing. He has adapted Sanskrit tradition of writing epics, (Mahakavya) and also, he has composed the epic on free verse. He has introduced and applied western Romantic trend of writing poetry. With these new modes, he has introduced new genre and approach in writing poems and other forms of literature. Openness, lucidity and honesty are some of the characteristics of Devkota’s poetic works. His feelings, sensibility and expressions have been blended perfectly and brilliantly with words and meanings that have created an explosion of thoughts and ideas in his writings. We find spontaneous expression in his poems and there is no artificial sense. As a versatile writer, he has composed in all literary genres, pomes, epics, essays, plays and fictions, but he is basically a poet. Having with the knowledge both in eastern Sanskrit literature and western literary traditions, he has combined both traditions in his Nepali writings. With the use of the western and eastern mythical references, he has united the traditions of the both in his writings. This article aims to observe his revisit to the eastern and western mythical references in Mayavini Circe, the epic on free verse.